Analisis Keterampilan Berbicara Terhadap Sikap Percaya Diri Siswa Kelas Tinggi Sekolah Dasar - Defi Antika; Juni Sahla Nasution; Lutfi Aulia; Syahrani Yumna Irfani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aspect of language skills that a student needs to master and understand after listening is speaking skills. Speaking skills are very important in everyday life because humans are social creatures who talk to other people every day. The ability to pronounce sounds or articulate words to express, express thoughts, ideas and feelings is called speaking. Speaking skills are one of the skills that students want to develop. This type of research is library research, namely research carried out by analyzing and using written literature in the form of books, scientific journals and newspapers as the main source. This library research research approach is qualitative, namely research that emphasizes the analysis of previously existing data. The results of the research in the form of reading skills are really needed by elementary school students, especially high class students, to encourage their self-confidence. As we know, elementary school students, especially high class students, tend to have more social interactions both at school and outside school and are usually asked by teachers to do more work. group assignments, therefore speaking skills are the most important thing.